(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In article development of modern Islamic thought is considered. The ratio of modernization and tradition, orthodoxy and an innovative approach in the history of modern Islam is analyzed. The author of article emphasizes existence of internal mechanisms of self-development of Islam that proves to be true Koran ayatollahs and authoritative opinions of scientists of Islam. And also the author considers the Jadids as the progressive phenomenon, the made huge impact on mood of the Muslim population of the Volga region, the Caucasus and Central Asia. Keywords: Islam, modernization, traditionalism, religious outlook, reformation, jadidism.